Analyst the Investor Intention on Socially Responsible Investment in Batam Using the Theory Of Planned Behavior Moderated by Religion - Yandi suprapto; Wirren Chang; Hesniati (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2024)
This study aims to study the investors intention to invest on socially responsible investment (SRI) using a theory called the planned behavior theory, the main research for this study consist of attitude, environmental attitude, social self-efficacy, and subjective norm moderate by religion. In this study, cross sectional data collected using a self-managed questionnaire by looking at several references from previous studies which then been made via Google form and distributed randomly to investors in Batam for 5 months. The sample uses "snowball sampling" with a bare minimum number of respondents is 384 respondents. 384 respondents were collected as a sample, and the results showed that attitude, environmental attitude, self-efficacy, and subjective norm had a strong relationship with the intention to invest in socially responsible investments, while religion did not have a significant moderating effect, and was found to have no significant relationship between variables. This research contributes to both academic research and practical applications in promoting socially responsible investing in Batam while considering the influence of religious beliefs.